2018
DOI: 10.1155/2018/5697092
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Temporal Distribution of Extrasystoles in Septic ICU Patients: The Feasibility of Predicting Fluid Responsiveness Using Extrasystoles

Abstract: Background Extrasystoles may be useful for predicting the response to fluid therapy in hemodynamically unstable patients but their prevalence is unknown. The aim of this study was to estimate the availability of extrasystoles in intensive care unit patients diagnosed with sepsis. The study aim was not to validate the fluid responsiveness prediction ability of extrasystoles. Methods Twenty-four-hour ECG recordings from a convenience sample of 50 patients diagnosed with sepsis were extracted from the MIMIC-II wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Prior to initiating the study, the expected occurrence of extrasystoles was determined retrospectively inspecting ectopic activity as captured by the Philips ® monitoring system from 59 cardiac surgeries. Approximately 70% of patients had at least one extrasystole, which was similar to a previous study [30]. Estimating conservatively, we therefore planned to include 60 patients.…”
Section: Statistical Analysis and Classificationmentioning
confidence: 54%
“…Prior to initiating the study, the expected occurrence of extrasystoles was determined retrospectively inspecting ectopic activity as captured by the Philips ® monitoring system from 59 cardiac surgeries. Approximately 70% of patients had at least one extrasystole, which was similar to a previous study [30]. Estimating conservatively, we therefore planned to include 60 patients.…”
Section: Statistical Analysis and Classificationmentioning
confidence: 54%
“…An important aspect of this method is therefore also the availability of ventricular extrasystoles, which the present study does not address in an adequately systematic way. However, we recently showed that in septic ICU patients, 76% of patients (32 out 42) with analyzable ECGs had at least one ventricular extrasystole in their 24h ECG recording, of which most were recorded on the first day of ICU admission [18]. In subjects with atrial fibrillation or other frequent arrhythmias such as trigemini, this method cannot be considered.…”
Section: Discussionmentioning
confidence: 99%